Ambidextrous Innovation in Project Management: A Systematic Literature Review - Mohammad ALSAIED; Patrick MCLAUGHLIN (Communications of International Proceedings, 2023)
Organizations increasingly rely on innovation to achieve sustainable competitive advantage and ensure longer-run market performance. Ambidextrous innovation is a critical strategic framework that guides managers to channel their innovation into exploring new ideas for products, services, and processes and exploiting ideas for improving existing ones. Ambidextrous innovation is one of the key frameworks that the projects can use to build innovation that best satisfies the stakeholder demands of higher performance at the lower resources. Ambidextrous innovation is becoming the most preferred framework for organizations to undertake innovations due to its ability to balance both the development of new and the improvement of existing products. However, research on ambidextrous innovation in the context of project management is widely lacking. Therefore, to fill such an important void in the literature, the present research has attempted to uncover the current state of knowledge on ambidexterity in project management using the systematic literature review as a research methodology based upon PRISMA framework.  The results of the review have revealed that ambidexterity plays an important role in enhancing project success and stakeholder satisfaction. The findings of the review have organizational culture as the important and critical antecedent of successful ambidexterity in project management. It shows that a culture that values new ideas can enable ambidextrous innovation in project settings. The research also offers an actionable direction to future researchers to develop the literature on ambidexterity in the project management context.
Keywords: Exploration; Exploitation; Organization; Culture; Ambidexterity; Innovation